Association between new-onset liver cirrhosis and suicide risk in South Korea: A nationwide cohort study - Suk-Yong Jang; Woo Sun Rou; Seok Hyun Kim; Byung Seok Lee; Hyuk Soo Eun (Clinical and Molecular Hepatology, 2021)
Background/Aims Current evidence suggests that liver cirrhosis (LC) causes severe psychological stress and depression, which are risk factors for suicide. Although previous studies reported the association between LC and suicidal thoughts, little is known of its effect on suicidal deaths. Therefore, this study was undertaken to investigate the effect of new-onset LC on suicide. Methods From the National Health Insurance Service-National Sample Cohort of South Korea, 5,809 incident LC patients and 11,618 risk-set controls matched by propensity score were selected for follow-up. The incidence rate of suicide was estimated using a generalized estimating equation with a Poisson distribution. Effect size was presented as a hazard ratio (HR) using Cox’s proportional hazards model. Results The incidence rate of suicide was 143.3 cases per 100,000 person years (95% confidence interval [CI], 100.2–205.1) among the LC cohort. The LC patients were 2.37 times more likely to commit suicide compared with matched controls (HR, 2.37; 95% CI, 1.44–3.88). Increased suicide risk was evident within the first 2 years of the follow-up period (HR, 2.59; 95% CI, 1.20–5.60) and among the 18–49-year-old age group (HR, 3.72; 95% CI, 1.45–9.56). Conclusions Our study found increased risk of suicide in patients with new onset LC, especially during the early period following diagnosis and in younger patients. To decrease this suicide risk, a regular and continuous social support system is required.